Cognitive and body manifestations of driving anxiety according to different onsets. Issue 6 (2nd November 2021) - Hidalgo-Muñoz, Antonio R.; Evennou, Myriam; Collette, Boris; Stephens, Amanda N.; Jallais, Christophe; Fort, Alexandra
Abstract: Background: Driving anxiety can have deleterious effects not only on driving behavior, but also on life quality. The interaction between motor vehicle collision (MVC) experiences and driving anxiety has been studied from different standpoints. However, the comparison with other events triggering it has been scarcely considered. Objectives: To analyze the body manifestations and the driving cognitions related to the accident, social and panic concerns in people suffering from different levels of driving anxiety. Method : A total of 260 participants suffering from driving anxiety were included in a survey, including Driving Cognition Questionnaire and Body Sensation Questionnaire. Results: Panic attacks and criticisms are the most relevant onsets of driving anxiety, more than MVC. Only 11.4% of MVC victims considered it as the onset. People with MVC history showed lower scores in social concerns than people without MVC experience and neither the responsibility of the MVC nor the role (driver/passenger) seemed to have an impact on the anxiety level. Conclusions: Although the most relevant body sensations, heart palpitations and sweating, were the same in people with panic attack experiences and MVC victims, a discrimination of the emotions behind the concept of "driving anxiety" is desirable to clarify the psychological effects of different onsets.